Analisis Usahatani dan Faktor-Faktor yang Mempengaruhi Pendapatan Usahatani Jeruk Gerga di Desa Rimbo Pengadang Kecamatan Rimbo Pengadang Kabupaten Lebong - Fery Murtiningrum; Eddi Silamat (Seminar Nasional Lahan Suboptimal, 2018)
Murtiningrum et al, 2019. An Analysis of Farming and its Factors Toward Gerga Orange Farming Revenue at Rimbo Pengadang Village, Rimbo Pengadang District, Lebong Regency. pp. 338-346. In Bengkulu Province, especially at Lebong Regency is one of the regions which has various potentials that support the national economy, both agriculture, plantation, fisheries, livestock and forestry potential. In agriculture, it is an area that suitable for developing various types of horticultural crops such as gerga oranges, because it is supported by loose and fertile soil conditions and also supported by altitudes ranging from 800-1000 masl. One of the gerga oranges producing areas in Lebong Regency is Rimbo Pengadang Village, Rimbo Pengadang District. Gerga oranges cultivation run by farmers is in accordance with the existing production factors, with the hope that they will get a profitable revenue for their families. This study aimed to determine the revenue of oranges farming in Rimbo Pengadang Village, to determine the effect of land area, age, education, and number of family dependents on oranges farming revenue in Rimbo Pengadang Village and to know the development of gerga culture in Rimbo Pengadang Village in the last 5 years. The data used are primary data and secondary data. The data analysis tool used PD = TR - TC, where: Pd = Agricultural revenue (Rp / Ut). TR = Total revenue (Rp / Ut) and TC = Total cost (Rp / Ut). The method used to determine the efficiency of sawn oranges farming used in the formula: R / C Ratio. To examine the factors that influence agricultural revenue, multiple linear analysis was used, with the following formula: From the results of the study, it is known that the average revenue of the orange saw farming business is Rp. 59.759.158,52  per year / UT. With an average revenue of Rp. 80.425.000 per year / UT. For Gerga oranges farming activities, the average cost is Rp. 20.665.841,48 per year / UT. And it found that of the 4 independent variables tested, the land area has a significant effect on revenue with t table> t count, amounting to 2,394. Meanwhile, if the F test carried out together, then the fcount <ftabel was obtained, then Ho was accepted and Ha was rejected. Means together with independent veriabel there was no significant effect on the dependent variable in the revenue case.